Pochodzenie tkanin archeologicznych — analiza izotopowa strontu - Kaczmarek, Zofia (Studia Europaea Gnesnensia, 2012)
Recenzja książki: Karin Margarita Frei, Provenance of Pre-Roman Iron Age textiles — methods development and applications, Ph.D. thesis, Faculty of Humanities, University of Copenhagen, Copenhagen 2010, 146 s., Appendix 66 s.